The mentor leader Secrets to Building People & Teams That Win Consistently - Dungy, Tony (Carol Stream, Ill Tyndale House Publishers, 2010)
A different way to lead -- The mind-set of a mentor leader -- The maturity of a mentor leader -- The marks of a mentor leader -- The mandate of a mentor leader -- The model of a mentor leader : living the message -- The means of a mentor leader : maximizing team performance -- The methods of a mentor leader : the seven E's of maximizing potential -- The measure of a mentor leader : a life of significance
Keywords: Leadership--Religious aspects--Christianity. | Mentoring--Religious aspects--Christianity. | Leadership. | Mentoring